An analysis of practice activities and instructional behaviours used by youth soccer coaches during practice: Exploring the link between science and application - Ford, P. R.; Yates, I.; Williams, A. M. (Journal of Sports Sciences, 2010)
We examined the practice activities and instructional behaviours employed by 25 youth soccer coaches during 70 different practice sessions. We evaluated the extent to which these activities and behaviours differ from those shown in contemporary research to best facilitate skill acquisition. Nine coaches worked with the under-9 years age group and eight coaches each with the under-13 and under-16 years age groups; nine of those coaches were employed at the elite level, nine at the sub-elite level, and seven at the non-elite level. Coaches had players spend more time in activities that were deemed less relevant to soccer match performance, termed "training form" (e.g. physical training, technique and skills practices), than activities deemed more relevant, termed "playing form" (e.g. small-sided/conditioned games and phase of play activities). Coaches provided high levels of instruction, feedback, and management, irrespective of the activity in which players engaged. Few differences in practice activities and instructional behaviours were reported across skill and age groups, implying the absence of any notable age- or skill-related progression. Findings are discussed with reference to recent research in the areas of skill acquisition, motor learning, and expert performance.